Comparison of Breast Massage (Oxytocin Massage, Oketani Massage, and Marmet Massage) Against the Smoothness of Breast Milk from the Aspect of Baby's Sleep Frequency - Kasad; Meliani Sukmadewi Harahap; Nurdahliana; Noviyanti (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2022)
Background: The inability to meet breast milk production can be prevented in various ways, one of which is breast massage. The breast massage technique, at a certain point, is able to remove the blockage of blood vessels and energy blockages so that it will facilitate milk production. This study aims to determine the potential of breast massage (oxytocin massage, oketani massage, and marmet massage) to smooth breast milk from the aspect of the baby's sleep frequency. Methods: Study design method experimental with the control group. Samples were Primiparous postpartum mothers who gave birth normally and were divided into three groups, namely oxytocin massage intervention group, marmet massage, oketani massage, and control group. Data were analyzed in univariate, bivariate, and multivariate. Results: Breast massage (oxytocin, marmet and oketani) in primiparous postpartum mothers was effective in increasing the frequency of baby’s sleep. The frequency of the baby’s sleep before Marmet massage was 3.29 hours, and after Marmet massage was 5.29 hours. In the oxytocin massage intervention group, it was known that the average sleep frequency of babies before breast massage was 2.00 hours, and after breast, massage was 3.00 hours. Furthermore, in the Oketani massage intervention group, it was found that the average frequency of the baby’s sleep before breast massage was 2.00 hours, and after breast, massage was 3.00 hours. In the control group, it is known that the average sleep frequency of babies before breast massage is 0.57 hours and after breast massage is 0.71 hours. Conclusion: Oxytocin massage, marmet massage, and oketani massage have been shown to be effective in improving the smoothness of breast milk from the aspect of the baby's sleep frequency.